Analisis Total Coliform di Air dan Sedimen di Pesisir Jabon, Sidoarjo Jawa Timur - Joni Johanda Putra; Hanisya Putri Kania Mardika; Rima Oktavia Kusuma; Muh. Sulaiman Dadiono; Agung Setia Abadi (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
The aim of the research are to: (1) count the Total Coliform on water and sediment; (2) compare the physical, chemical and biology parameters to the ministry of environment regulation number 51, 2004 appendix 2 and appendix 3 ; (3) differentiate of Total Coliform on water and sediment and ; (4) grouping the parameters of environment and Total Coliform based on similar data by clusterring analysis. MPN method is used to count Total Coliform and fermentation method to detect coliform bacteria. Based on the Total Coliform are obtained, Total Coliform on water are 21-70 MPN/100 ml and Total Coliform on sediment are 110-9.000 MPN/100 ml. It can conclude that Jabon Coastal is indicates as a contaminated water based on Total Coliform bacteria.